2015
DOI: 10.1038/ejcn.2015.177
|View full text |Cite
|
Sign up to set email alerts
|

The co-occurrence of anemia and cardiometabolic disease risk demonstrates sex-specific sociodemographic patterning in an urbanizing rural region of southern India

Abstract: Background/ObjectivesTo determine the extent and sociodemographic determinants of anemia, overweight, metabolic syndrome (MetS), and the co-occurrence of anemia with cardiometabolic disease risk factors among a cohort of Indian adults.Subject/MethodsCross-sectional survey of adult men (n=3,322) and non-pregnant women (n=2,895) aged 18 y and older from the third wave of the Andhra Pradesh Children and Parents Study that assessed anemia, overweight based on Body Mass Index, and prevalence of MetS based on abdomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
3
16
1
Order By: Relevance
“…The burdens of moderate and severe anemia among the sample population were considerably higher than national figures (15.0% and 1.8%, respectively), underscoring the severity of anemia as a public health concern in the study region [ 3 ]. While there is a dearth of prevalence data on anemia among men in India, our study found one of the highest recorded prevalence estimates in India, considerably higher than the national rural average (24%) [ 3 ] and other regional populations in South India [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
“…The burdens of moderate and severe anemia among the sample population were considerably higher than national figures (15.0% and 1.8%, respectively), underscoring the severity of anemia as a public health concern in the study region [ 3 ]. While there is a dearth of prevalence data on anemia among men in India, our study found one of the highest recorded prevalence estimates in India, considerably higher than the national rural average (24%) [ 3 ] and other regional populations in South India [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 71%
“…Given the higher prevalence of both overweight and anemia among women as compared to female adolescents, it is not surprising that the prevalence of the individual‐level double burden among women far exceeded that of female adolescents. Despite the fact that the odds of anemia and overweight appear to be independent of one another in this population, the high prevalence of their co‐occurrence among women of reproductive age—analogous to other regions with a high prevalence of the individual‐level double burden of malnutrition (Gartner et al, ; Jones et al, )—suggests the need for policy and programmatic responses that address both forms of malnutrition in this demographic group.…”
Section: Discussionmentioning
confidence: 83%
“…External comparison of this specific issue of double burden inequalities with other countries is difficult as published data are scarce. In India, the subjects of the Hyderabad Nutrition Trial nevertheless also featured a higher prevalence of the double burden of overweight and anaemia among women v. men (9 % v. 1 %, respectively), although at much lower overall level mainly due to the much lower overall prevalence of overweight (32) . In our setting, gender differences in malnutrition measured from the point of view of this double burden resulted in much higher values than when each type of malnutrition was measured separately.…”
Section: Discussionmentioning
confidence: 97%
“…As our main interest was in gender inequality measures, the gender × covariate interactions terms were then detailed by assessing the variation of the women v. men RPR inequality measure according to the categories of the covariates (i.e. assessing the modifying effect of covariates on the associations between gender and health outcomes) (8,31) , rather than the other possible symmetric interpretation of the same interaction terms (assessing the modifying effect of gender on the relationship between health outcomes and covariates) (32) . Adjusted RPR were estimated based on marginal estimates of probabilities computed at the mean value of all other covariates using the margins command in Stata.…”
Section: Double Burden Of Malnutritionmentioning
confidence: 99%